The milepost : all-the-North travel guide. 2025. (Morris Communications Company, LLC, 2025)
This annually updated travel guide to Alaska and Northwest Canada is a must-have resource for travelers to these areas. "The Milepost" provides maps, diagrams, photographs, and an almost mile-by-mile travelogue of what to expect along the main roads.